The Diverged Trypanosome MICOS Complex as a Hub for Mitochondrial Cristae Shaping and Protein Import - Kaurov, Iosif; Vancová, Marie; Schimanski, Bernd; Cadena, Lawrence Rudy; Heller, Jiri; Bílý, Tomáš; Potesil, David; Eichenberger, Claudia; Bruce, Hannah; Oeljeklaus, Silke; Warscheid, Bettina; Zdrahal, Zbynek; et al. (Cell Press, 2018)
The mitochondrial contact site and cristae organization system (MICOS) is a multiprotein complex responsible for cristae formation. Even though cristae are found in all mitochondria capable of oxidative phosphorylation, only Mic10 and Mic60 appear to be conserved throughout eukaryotes. The remaining 4 or 5 known MICOS subunits are specific to the supergroup Opisthokonta, which includes yeast and mammals that are the only organisms in which this complex has been analyzed experimentally. We have isolated the MICOS from Trypanosoma brucei, a member of the supergroup Excavata that is profoundly diverged from opisthokonts. We show that it is required for the maintenance of the unique discoidal cristae that typify excavates, such as euglenids and kinetoplastids, the latter of which include trypanosomes. The trypanosome MICOS consists of 9 subunits, most of which are essential for normal growth. Unlike in opisthokonts, it contains two distinct Mic10 orthologs and an unconventional putative Mic60 that lacks a mitofilin domain. Interestingly, one of the essential trypanosomatid-specific MICOS subunits called TbMic20 is a thioredoxin-like protein that appears to be involved in import of intermembrane space proteins, including respiratory chain complex assembly factors. This result points to trypanosome MICOS coordinating cristae shaping and population of its membrane with proteins involved in respiration, the latter via the catalytic activity of TbMic20. Thus, trypanosome MICOS allows us to define which of its features are conserved in all eukaryotes and decipher those that represent lineage-specific adaptations.
Keywords: contact site; organizing system; intermembrane space; inner membrane; outer-membrane; mia pathway; brucei; organization; architecture; biogenesis